Phytoptidae Murray - Chetverikov, Philipp E.; Beaulieu, Frédéric; Cvrković, Tatjana; Vidović, Biljana; Petanović, Radmila U. (Zenodo, 2012)
Family: Phytoptidae Murray Diagnosis . Eriophyoid mites with 1–5 setae on the prodorsal shield, including unpaired or paired vi and/or paired ve setae; usually tibia I solenidion (ϕ) and opisthosomal subdorsal seta ( c1 ); female genital coverflap usually without ridges; spermathecal tubes short to very elongate (Amrine et al. 2003). Published as part of Chetverikov, Philipp E., Beaulieu, Frédéric, Cvrković, Tatjana, Vidović, Biljana & Petanović, Radmila U., 2012, Oziella sibirica (Acari: Eriophyoidea: Phytoptidae), a new eriophyoid mite species described using confocal microscopy, COI barcoding and 3 D surface reconstruction, pp. 41-60 in Zootaxa 3560 on page 44, DOI: 10.5281/zenodo.213624